Prevention of Online Game Addiction Through Increasing Self-Control - Anjani Widya Cahyaningrum; Ramon Ananda Paryontri (Green Publisher, 2024)
Excessive use of online games can result in negative impacts, such as an increased risk of addiction. Therefore, the purpose of psychoeducational activities is to provide understanding to junior high school students about the importance of improving self-control in using online games. Psychoeducational activities began with observation, interviews, pre-tests, and post-tests, as well as the delivery of material on self-control and online game addiction. In its implementation, it was found that as many as 20 students fell into the category of severe online game addiction, while 14 students fell into the low category. The results of psychoeducational activities showed an increase in students' understanding of self-control and online game addiction after receiving counseling. Psychoeducation helps students understand the risks of online game addiction and the importance of improving self-control in their use. Through this understanding, it is hoped that students can be wiser in managing the time and frequency of playing online games, and prevent addiction. Thus, psychoeducational activities have an important role in helping students develop awareness of the negative impact of excessive use of online games as well as increase their self-control in this regard.